2010
DOI: 10.1103/physrevb.81.224504
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle relaxation dynamics in spin-density-wave and superconductingSmFeAsO1xFxsingle crystals

Abstract: We investigate the quasiparticle (QP) relaxation and low-energy electronic structure in undoped SmFeAsO and near-optimally doped SmFeAsO0.8F0.2 single crystals-exhibiting spin-density wave (SDW) ordering and superconductivity, respectively-using pump-probe femtosecond spectroscopy. In the undoped single crystals a single relaxation process is observed, showing a remarkable critical slowing down of the QP relaxation dynamics at the SDW transition temperature TSDW125 K. In the superconducting (SC) crystals multi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
78
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 57 publications
17
78
0
1
Order By: Relevance
“…3 we show R/R transients at a few characteristic temperatures for both samples. Starting at T = 300 K we observe subpicosecond isotropic transients in both samples consistent with previous results in related iron-based pnictides [16][17][18]. With decreasing T the twofold anisotropy appears below ∼250 K in Eu-122 and ∼190 K in EuP-122.…”
Section: Experimental Datasupporting
confidence: 78%
“…3 we show R/R transients at a few characteristic temperatures for both samples. Starting at T = 300 K we observe subpicosecond isotropic transients in both samples consistent with previous results in related iron-based pnictides [16][17][18]. With decreasing T the twofold anisotropy appears below ∼250 K in Eu-122 and ∼190 K in EuP-122.…”
Section: Experimental Datasupporting
confidence: 78%
“…Usually the anomalous T dependence of τ exp is observed in many gapped systems, for example, phaseordered systems showing an energy gap opening in the electron band below the transition temperature T c . It has been found that a wide variety of superconductors [1][2][3][4][5][6][7][8][9][10][11][12][13] and density-wave compounds [14][15][16][17][18][19] show diverging behavior of τ exp near T c , as confirmed by femtosecond time-resolved optical spectroscopy. 1,4,5,[7][8][9][10][11][12][13][14][15][16][17]19 The divergence of τ exp in these gapped systems is believed to result from a recursive energy transfer between electrons and phonons.…”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, the change of the band structure may be attributed to a change on the Fermi surface supported by the pseudogap which causes the partial gapping of the Fermi surface. The pseudogap has actually been found from NMR [34] and photoemission experiments [35]; recently the quasiparticle relaxation dynamics on single crystal SmFeAsO 1-x F x [36] reveals the pseudogap with an onset above 180 K.…”
Section: Hall Effectmentioning
confidence: 99%